Squaric Acid Bisphposphonates for Theranostics of Bone Metastasis – the Easy DOTA-Zoledronate - Greifenstein, Lukas; Engelbogen, Nils; Máthé, Domokos; Grus, Tilmann; Rösch, Frank; Bergmann, Ralf (Frontiers in Nuclear Medicine, 2022)
Bisphosponates are an interesting molecular class and in recent years their application has found its way into radiopharmaceutical research and thus into molecular imaging. In addition to great imaging of bone metastases, bisphospnate-based tracers for imaging also have some significant drawbacks. For example, their synthesis is often difficult. Additionally, this can lead to complex and almost impossible purification and quality control. This has limited the production and labeling of suitable molecular and their widespread use to a few facilities. Our squaric acid-based approach provides a way to overcome these problems and makes the synthesis as well as the purification of the compounds much easier. In addition, we were able to demonstrate that labeling with 68Ga is possible under the typical conditions.